Bahan Ajar Digital untuk Pembelajaran Bahasa Berbasis Tugas Bermuatan Pendidikan Lingkungan: Sebuah Studi Analisis Kebutuhan dan Respons Guru - Syahrul Ramadhan; Atmazaki Atmazaki; Vivi Indriyani; Elfia Sukma (Universitas Negeri Padang, 2023)
The COVID-19 pandemic is having a major impact on education. The teacher must try to make adjustments so that the learning process is carried out and achieves learning objectives. Based on the survey, teaching materials are still dominated by the use of printed teaching materials, even though learning has been done online. In addition, the approach used is dominated by task-based learning but does not follow the order of the approach that should be (according to theory). Furthermore, language learning not only aims to develop language skills, but also contains knowledge that is useful for students and the environment, one of which is environmental education. The purpose of this research is to develop task-based digital teaching materials with environmental education. The type of research used is development research using the Plomp Model (Preliminary Research, Prototype Phase, & Assessment Phase). The data analysis technique used in this research is descriptive data analysis technique. The results showed that it is necessary to develop teaching materials for language learning. Based on the teacher's response to the teaching material model, it shows a positive response to be used in learning